Death is that man taking names : intersections of American medicine, law, and culture - Burt, Robert A., 1939-2015 (University of California Press ; Milbank Memorial Fund, 2002)
The American culture of death changed radically in the 1970s. For terminal illnesses, hidden decisions by physicians were rejected in favor of rational self-control by patients asserting their "right to die"--Initially by refusing medical treatment and more recently by physician-assisted suicide
Includes index.
Notes: p. 187-218.
Keywords: Death.; Terminal care -- United States.; Death -- Social aspects -- United States.; Death; United States; Mort -- Aspect social -- États-Unis.; Soins en phase terminale -- États-Unis.; Mort.; deaths.; SOCIAL SCIENCE -- Death & Dying.; FAMILY & RELATIONSHIPS -- Death, Grief, Bereavement.; MEDICAL -- History.; Death -- Social aspects; Terminal care